PENCIPTAAN DAN PELATIHAN TARI KREASI ANDRAWINA PUNJULHARJO” (STUDI KASUS : DESA PUNJULHARJO, KABUPATEN REMBANG) - Muhammad, Fuad; Aurely, Anastasya Putri; Devara, Hafiz Rama; Triyono, Triyono; Abdillah, Rangga Fajar; Hadiyanto, Hadiyanto; Dewi, Indahsari Kusuma (Universitas Mataram, 2025)
The Andrawina Creation Dance is a new creative dance created to depict the rich traditions and dynamics of changes that occur in Punjulharjo Village. This dance reflects the community's enthusiasm and dedication in preserving traditions and livelihoods in the field of salt farming. The aim of this activity is to create works of art that are relevant to local cultural values and encourage the involvement of the younger generation in traditional art. This dance was created through improvisation and music analysis methods. Dance movements are formed spontaneously by paying attention to the tempo and melody of the accompanying music. This dance is performed by at least 5 dancers and combines traditional and modern elements. The results of this activity show the high enthusiasm of village children in participating in dance training which is held every evening. Andrawina's dance was successfully performed in the arts event